Organizational communication of the hatch indonesia - Melati Hendaryani (INJECT (Interdisciplinary Journal of Communication), 2020)
This research aims at understanding external and internal organizational communication practiced by The Hatch Indonesia using the organizational communication concept by Onong U. Effendy in the book of Poppy Ruliana. The Hatch Indonesia is a talent incubator organization focused digital marketing field that aims to improve the college students’ ability to be ready to work in the industry. This research expects to contribute to organizational communication studies as well as an indicator of organizational communication practiced by The Hatch Indonesia. The data in this research ware collected by deep semi-structured interviews and observation. This study uses the interpretive paradigm to discover and understand external and internal organizational communication at The Hatch Indonesia. The research uses the descriptive study with the analytical technique by Miles and Huberman. The findings in this research decipher organizational communication practiced by The Hatch Indonesia in developing talent in the digital marketing field.